THE RELATION OF ARECA NUT CHEWING HABIT FREQUENCY AND DURATION TO THE INCIDENCE OF CHRONIC PULMONARY OBSTRUCTIVE DISEASE (COPD) - Christanto, Anthony; Sumali, Lindayanti (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Areca nut chewing habit is a widespread habit in Indonesia. This habit has several negative health effects, including to the respiratory system. One of its effects towards the respiratory system is the impairment of lung function. Chronic Obstructive Pulmonary Disease (COPD) is a progressive and permanent pulmonary disease that impairs the lung function. Methods: This study is an analytical observational study with cross-sectional approach. Subjects are non-smoking patients aged more than 40 y.o, with total samples fulfilling the inclusive and exclusive criterias being 150 samples. This study is conducted in the GP clinic, specialist clinic, and emergency unit of St. Carolus Borromeus Hospital Kupang from March 2017 to March 2018. Lung functions are obtained using spirometry to diagnose COPD, and informations from the samples are obtained using a questionnaire. Datas are then processed using appropriate statistic tests. Results: There is stastistically significant relation between areca nut chewing habit and the incidence of COPD (p=0,041). There is also a significant relation between the frequency (p=0,018) and duration (0,013) of areca nut chewing habit and the incidence of COPD. Additionally, we found that FEV1/FVC ratio means are lower in those with frequent (>5 days/week) and long duration (20 years) of areca nut chewing. Conclusions: There is a significant relation between the arena nut chewing habit and its frequency and duration with the incidence of COPD.